Surgical correction of truncus arteriosus in infancy - Sullivan, Henry; Sulayman, Rabi; Replogle, Robert; Arcilla, Rene A. (The American journal of cardiology, 1976)
An 8 week old infant with severe heart failure from type 1 truncus arteriosus underwent successful corrective surgery employing the Rastelli procedure with use of deep hypothermia and total circulatory arrest. Postoperative hemodynamic studies showed complete closure of the septal defect, disappearance of truncal stenosis, but presence of mild porcine valve stenosis. This procedure is possible even in very small subjects and is preferable to palliative pulmonary arterial banding.